Somos educados para um genocídio alimentar? O complexo da alimentação na crise estrutural do capital e seus desdobramentos nas políticas educacionais - Souza, Felipe Guilherme de (2018)
The thesis pursues a historical question of humanity, that is, how to feed all individuals in a process of human emancipation. For its development, we are based on the marxian ontology, from which labour is understood as a vital category in the origin and unfolding of the social being, placing in its dynamics the relationships that have been established between education and nourishment. Thus, we find that the origin of the food genocide comes from the fragmented organization of society into social classes, from the agricultural revolution in the Middle East, expanding to other regions over thousands of years until its current capitalist conformation. Many authors, including Friederich Engels and Karl Marx, point to this social murder in food as an essential phenomenon in the exploitation of the labour class for the reproduction of capital. In today's scenario, where provisions are more than enough for all people, we find in the world food a process constituted by hunger and other health problems arising from the logic of destructive production and the waste of natural resources, which we call degeneracy. Faced with this reality, the bourgeois state has been seeking answers to this problem, which implies the call of the educational complex to try to soften without compromising society centered on capital reproduction. Thus, we investigate some proposals for food education, divided into two main groups: on the one hand, those measures whose ultimate purpose is to benefit sectors directly linked to agribusiness and, on the other, those that excel in the conciliation of antagonistic interests of the working class with those of the large food industries. In the political-economic sphere, the differences are, respectively, in the neoliberal proposal, to increase capital at any cost, and in the attempt to expand democracy to a desired humanization of capital. Beyond the market proposal and the perspective of citizenship, our studies point to the impossibility of eliminating human degeneration without destroying the reproductive logic of capital. In this sense, we perceive in policy measures that reach the surface of this food genocide, and point to the need to overcome class struggle, as essential in a genuinely human diet, in which food can be produced and consumed in a conformation directed towards human emancipation, without the dependence of the market or the state, that is, the reverse of the needs placed to maintain any form of reproduction of the social being grounded in the relations of exploitation of labor.